Optimalisasi Penyelesaian Pembiayaan Bermasalah Pada BMT Kota Mandiri Bengkulu - Wardah, Khairiah El (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The high amount of problematic financing at BMT Kota Mandiri Bengkulu caused this institution to experience losses so that its operations became stuck. This study aims to determine how the optimization carried out by BMT Kota Mandiri in solving problematic murabahah financing. The type and approach of the research is descriptive qualitative. The technique of collecting data was carried out by observation, interviews and documentation. The main informant is Mrs. Hesti, the treasurer of BMT Kota Mandiri. The data analysis technique used was the Miles and Huberman model. The results of this study indicate that BMT Kota Mandiri performs optimization by increasing the intensity of communication with customers, helping to promote customers who have products (entrepreneurship), providing good advice to customers regarding the business being carried out, and always reminding customers to pay off installments through tausiyah. short messages related to debts in Islamic teachings through short messages sent via SMS and WA.